Surface modification of biomaterials to reduce polyethylene wear in metal-polymer contact / Tan Mean Yee - Tan, Mean Yee (2020)
This research focus on studying different surface modification (Texturing and DLC coating) on the metal part of TKR (Total knee replacement) in improving UHMWPE (Ultra-high molecular weight polyethylene) wear. TKR was widely being used to relieve knee pain due to osteoarthritis and further restore knee function of patients. Generally, TKR consists of metal femoral component, metal tibial component, and UHMWPE tibial insert. TKR will fail due to various factors over time, however, this study will be focusing on failure cause by loosening. Loosening failure of TKR was mainly caused by wear debris generated during articulation motion, where UHMWPE wear was one of the main threats toward loosening failure. UHMWPE has many advantages; however, the major drawback of UHMWPE was its hydrophobicity. Protein will more likely being attracted and denatured onto hydrophobic surface and form protein aggregate. The protein aggregates formed on the surface will increase surface roughness and friction which later cause surface wear. However, when two hydrophobic surfaces with protein aggregates interact, protein aggregate from both surfaces will bind together and formed a thin film which protects the surface from wear. Hence, surface modification (Texturing and DLC coating) onto the hydrophilic metal surface will be done in order to alter the surface energy of the metal surface. Surface texturing using LST method was used to create dimple texture, while surface coating was used to deposit DLC (Diamond-like coating) coating (ta-C, a-C:H) onto the metal surface. Surface characterization (RAMAN, FTIR) was done in order to characterize the surface morphology before wear. Protein absorption and wettability test was done on DLC coating in order to evaluate the relationship between surface energy and protein adsorption towards wear. Wear test was done using reciprocating and pin-on- disc method under protein (BS, BSA) lubricated condition. Wear surface then was characterized using RAMAN, FTIR, SEM, optical microscope in order to analyze the surface wear mechanism. The results of this research show that UHMWPE wear of tibial insert in TKR will deteriorate over time and was essential to reduce formation of wear in order to improve functionality and performance of TKR. Hence, surface modification was being done. Surface texturing might have the ability to protect its own surface from wear, but it will cause high wear on its counterpart. While DLC coating has the ability to protect its own surface and its counterpart from wear. a-C:H coating can reduce more UHMWPE wear as compared with ta-C coating. The a-C:H coating deposited using different hydrocarbon source will not have much differences in improving UHMWPE wear.